A rhomboid protease gene deletion affects a novel oligosaccharide N-linked to the S-layer glycoprotein of Haloferax volcanii - Parente, Juliana Elena (2014)
Rhomboid proteases occur in all domains of life; however, their physiological role is not completely understood, and nothing is known of the biology of these enzymes in Archaea. One of the two rhomboid homologs of Haloferax volcanii (RhoII) is fused to a zinc finger domain. Chromosomal deletion of rhoII was successful, indicating that this gene is not essential for this organism; however, the mutant strain (MIG1) showed reduced motility and increased sensitivity to novobiocin. Membrane preparations of MIG1 were enriched in two glycoproteins, identified as the S-layer glycoprotein and an ABC transporter component. The H. volcanii S-layer glycoprotein has been extensively used as a model to study haloarchaeal protein N-glycosylation. HPLC analysis of oligosaccharides released from the S-layer glycoprotein after PNGase treatment revealed that MIG1 was enriched in species with lower retention times than those derived from the parent strain. Mass spectrometry analysis showed that the wild type glycoprotein released a novel oligosaccharide species corresponding to GlcNAc-GlcNAc(Hex)2-(SQ-Hex)6 in contrast to the mutant protein, which contained the shorter form GlcNAc2(Hex)2-SQ-Hex-SQ. A glycoproteomics approach of the wild type glycopeptide fraction revealed Asn-732 peptide fragments linked to the sulfoquinovose-containing oligosaccharide. This work describes a novel N-linked oligosaccharide containing a repeating SQ-Hex unit bound to Asn-732 of the H. volcanii S-layer glycoprotein, a position that had not been reported as glycosylated. Furthermore, this study provides the first insight on the biological role of rhomboid proteases in Archaea, suggesting a link between protein glycosylation and this protease family.